Partisan Conflict and Stock Price - HUANG, Dashan (Institutional Knowledge at Singapore Management University, 2018)
Partisan conflict has been one dominant theme in U.S. politics in recent years. By using the textual index of Azzimonti (2018), this paper shows that partisan conflict positively predicts market returns, controlling for economic predictors and proxies for uncertainty, disagreement, geopolitical risk, and political sentiment. A one standard-deviation increase in partisan conflict is associated with a 0.58% increase in next month market return. The forecasting power concentrates in periods when the president is from the Republican Party or the majority of House is Republicans. Partisan conflict is positively related to downside risk, and makes investors more conservative when its value increases.